(untitled) (City: History, Culture, Society, 2022)
How can we interpret the architects’ desire to look postmodern in the last decade of soviet architecture (1980-1990)? Can it be explained according to René Girard’s theory of ’mimetic desire’? How much was it an imitation of Western forms, and how much was it connected to the vernacular turn, resulting in irreverent ’overuse’ of historical references? Emphasis on the genius loci, vernacular elements, and search for historical/cultural identity indicates that themes usually associated with the postmodern architecture surfaced in the Eastern Bloc long before the demise of the socialist political system. The paper is focused on the 1980s architectural competitions in Vilnius, Lithuania, where younger generations of architects presented postmodern designs that widely employed historical references